Impact of Artificial Intelligence on Mathematics Graduate Employability and Sustainability of Mathematics Education in Nigeria - OYENIRAN, Joy Omolola; ADEBIYI, Lawrence Adesola (Ilorin Journal of Education, 2025)
Artificial Intelligence occurred as a transformative technology in Mathematics which offers both opportunities and challenges to Mathematics education. Studies have shown that AI has positive effect as it can improve students’ learning performance but the fear of taking mathematics graduate out of job is at play. This study employed a survey research design to investigate the impact of artificial intelligence (AI) on Mathematics graduates’ employability and the sustainability of Mathematics education in Nigeria. A simple random sampling technique was adopted to select one hundred and fifty respondents for the study. One research question was answered while three hypotheses were tested at the 0.05 level of significance by using a questionnaire to elicit information from the respondents. The questionnaire tagged Impact of AI on Mathematics Graduate Employability (IAIMGE) has cronbach-Alpha value of 0.78. A significant difference was discovered in the Mathematics lecturers’ opinion on the effect of AI on Mathematics graduate employability and Mathematics education sustainability based on gender and institution location (N=150; df=148; t=3.195; p=.05) and (N=150; df=148; t=3.012; p=.05), respectively. There was also a significant difference in the opinion of the lecturers based on institution type F(2,147)=3.182, p<0.05). It was also discovered from the study that most Mathematics lecturers have not been using AI in their teaching, and they mainly believe that the use of AI in teaching Mathematics is a threat to Mathematics graduate employability. Most of them, however, believed that a Mathematics graduate will be of advantage in using AI if they develop their mathematical skill technologically. The study recommended that Mathematics lecturers should imbibe the use of AI in their teaching and instill in their students the opportunity of using their mathematical knowledge to develop AI which will take away any form of threat on their employability for sustainable Mathematics education in Nigeria.